نشاط الوطنيين في المنطقة الدولية طنجة 1923-1956م - بوغزالة محمد , صحراوي , زهية عائشة (جامعة الوادي University of eloued, 2018)
تجلّت البوادر الأولى للنّشاط الوطني بطنجة من خلال الحركة السّلفيّة الإصلاحيّة، وكان من أبرز دعاتها بالمدينة الشّيخ عبد الله السّنوسي والشيخ محمّد العربي العلوي من خلال الدروس التي كان يلقيانها بالجامع الأعظم، كما برزت جماعة لسان المغرب التي أخذت على عاتقها مهمة إصلاح الأوضاع المتردية من خلال تبنّيها لمشروع دستور 1908م، وقد تدعّم هذا النّشاط ببروز حركة ثقافيّة نشطة تجلّت في نشاط الجمعيات وحركة المدارس الحرّة والاحتفال بعيد المولد النبوي الشريف...، ومع صدور الظّهير البربري 16 ماي 1930م تصاعدت وتيرة النّشاط الوطني بالمدينة على غرار المدن المغربيّة الأخرى وتزامن ذلك مع النّضج الذي وصلت إليه العناصر الوطنيّة بفضل الاحتكاك بشخصية الأمير شكيب أرسلان، والّتي زاد تأثيرها بعد زيارته لطنجة وتطوان أوت 1930م، غير أنّ هذا النّشاط لم يكن سوى بداية لمرحلة جديدة من النّضال ستشهده المدينة مع انطلاقة العمل الوطني بشكله المنظّم بتأسيس فرع كتلة العمل الوطني 1934م ومن بعده فرع الحزب الوطني 1937م والّذي أدّى فيه وطنيّو طنجة على رأسهم عبد الله كنون الدّور البارز خاصّة في ربط الصّلة بين الدّاخل والخارج مستغلين في ذلك طبيعة مدينة طنجة الدّوليّة والّتي سيبرز دورها أكثر بعد نهاية الحرب العالميّة الثّانية بعودة الحماية الدّوليّة من جديد للمدينة ودخول الولايات المتّحدة الأمريكيّة كطرف فاعل في نظام الحماية فضلاً عن زيارة السّلطان محمد الخامس لها في أفريل 1947م، خاصّة بعد لجوء العديد من الوطنيّين إليها على رأسهم زعيم حزب "الوحدة المغربية" محمّد المكّي النّاصري، زعيم حزب "الإصلاح الوطني" عبد الخالق الطريس، زعيم حزب "الاستقلال" علال الفاسي حيث هيّأ لهم هذا المناخ ممارسة نشاطهم سواءً بشكل فردي أو جماعي بتأسيس الجّبهة الوطنيّة أفريل 1951م، هذا الدّور الذي جسّدته العناصر الوطنيّة لم يتوقف عند هذا الحد فبمجرد انطلاقة العمل العسكري انخرطت العناصر الوطنيّة في طنجة في هذا الميدان مستغلّة ما تتيحه المدينة من إمكانيات لتكون المزوّد الرئيسي للمنطقة السّلطانية بالسّلاح. The first signs of national activity in Tangier were manifested through the Salafist reform movement. Among the most prominent advocates in the city were Sheikh Abdullah Al-Senoussi and Sheikh Mohammed Al-Arabi Al-Alawi through the lessons they gave at the Grand Mosque. The Tongue Group of Morocco also took the task of reforming the deteriorating situation through Adoption it To the draft constitution of 1908, and this activity has been supported by the emergence of an active cultural movement manifested in the activity of associations and the movement of free schools and the celebration of the birth of the Prophet Muhammad ... With the issuance of the Berber dahir May 16, 1930, the pace of national activity in the city, This coincided with the maturity achieved by the national elements thanks to friction with the personality of Prince Chakib Arslan, which increased its impact after his visit to Tangier and Tetouan in 1930, but this activity was only the beginning of a new phase of the struggle will witness the city with the start of national action in the form organized by the establishment of a branch The National Labor Party in 1934 and the National Party branch in 1937 which led the patriots of Tangier, led by Abdullah Kannoun, the prominent role, especially in linking the link between the home and abroad, taking advantage of the nature of Tangier International, which will emerge more after the end of World War II To protect the international back to the city and the entry of the United States of America as an active party in the protection system as well as the visit of Sultan Mohamed V in April 1947, especially after the resort of many nationalists, headed by the leader of the "Moroccan unity" Mohammed al-Makki Nasseri, Abd al-Khaleq al-Taris, the leader of the Independence Party, Allal El-Fassi. This atmosphere created their activity both individually and collectively by establishing the National Front in April 1951. The role played by the national elements did not stop at this point. In this field, taking advantage of the city's potential to be the main supplier to the region of the weapons.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي الحديث والمعاصر
Keywords: طنجة , نشاط الوطنيين , المغاربة; Tanger, l'activité des patriotes, des marocains; Tangier, the activity of patriots, Moroccans